SOX9 and SRY binding sites on mouse mXYSRa/Enh13 enhancer redundantly regulate Sox9 expression to varying degrees. Issue 1 (3rd August 2022) - Ogawa, Yuya; Terao, Miho; Tsuji-Hosokawa, Atsumi; Tsuchiya, Iku; Hasegawa, Midori; Takada, Shuji
Abstract: Sox9 plays an essential role in mammalian testis formation. It has been reported that gene expression in the testes is regulated by enhancers. Among them, mXYSRa/Enh13—which is located at far upstream of the transcription start site—plays a critical role, wherein its deletion causes complete male-to-female sex reversal in mice. It has been proposed that the binding sites (BSs) of SOX9 and SRY, the latter of which is the sex determining gene on the Y chromosome, are associated with mXYSRa/Enh13. They function as an enhancer, whereby the sequences are evolutionarily conserved and in vivo binding of SOX9 and SRY to mXYSRa/Enh13 has been demonstrated previously. However, their precise in vivo functions have not been examined to date. To this end, this study generated mice with substitutions on the SOX9 and SRY BSs to reveal their in vivo functions. Homozygous mutants of SOX9 and SRY BS were indistinguishable from XY males, whereas double mutants had small testes, suggesting that these functions are redundant and that there is another functional sequence on mXYSRa/Enh13, since mXYSRa/Enh13 deletion mice are XY females. In addition, the majority of hemizygous mice with substitutions in SOX9 BS and SRY BS were female and male, respectively, suggesting that SOX9 BS contributes more to SRY BS for mXYSRa/Enh13 to function. The additive effect of SOX9 and SRY via these BSs was verified using an in vitro assay. In conclusion, SOX9 BS and SRY BS function redundantly in vivo, and at least one more functional sequence should exist in mXYSRa/Enh13.